Commonwealth and sea-level rise - Hamilton, Clive (2003)
Notes that for many Commonwealth countries, climate change is the most serious threat to their future. Looks at the Commonwealth principles and climate change. Examines the politics of climate change and reports on the developments at CHOGM 2002.